+0  
 
0
150
1
avatar

5(1+2)^2-4(3-1)^3-6(2+3)^4=???

Guest Feb 10, 2017
Sort: 

1+0 Answers

 #1
avatar+5553 
+1

5(1+2)^2-4(3-1)^3-6(2+3)^4

 

= 5(3)^2 - 4(2)^3 - 6(5)^4

 

=5(9) - 4(8) - 6(625)

 

= 45 - 32 - 3750

 

= -3737

hectictar  Feb 10, 2017

17 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details